1998
DOI: 10.1111/j.1749-6632.1998.tb10177.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative 5‐ht5 Receptors: Localization in the Mouse CNS and Lack of Effect in the Inhibition of Dural Protein Extravasation

Abstract: Putative 5-ht5 receptor binding sites were visualized by in vitro autoradiography using [125I]LSD (in the presence of clozapine and spiperone) or [3H]5-carboxamidotryptamine (in the presence 8-OH-DPAT, GR127935 and spiperone). Under these conditions, no [3H]5-carboxamidotryptamine labeling was detected in the brain of mice lacking the gene encoding the putative 5-ht5a receptor (knockout mice), whereas intermediate densities of binding sites were seen in the olfactory bulb and neocortex of wild-type mice. [125I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The physiological function of 5-ht 5B autoreceptors would most likely depend on their cellular location on cell bodies, dendrites and/or terminals of 5-HT neurons. To our knowledge, one single report has addressed the issue of the anatomical distribution of 5-ht 5B receptor binding sites (Waeber et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological function of 5-ht 5B autoreceptors would most likely depend on their cellular location on cell bodies, dendrites and/or terminals of 5-HT neurons. To our knowledge, one single report has addressed the issue of the anatomical distribution of 5-ht 5B receptor binding sites (Waeber et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of selective ligands for 5-ht 5 receptors has hindered a thorough pharmacological characterization, and the analysis of their localization and of their functional implications. Attempts to explore the autoradiographic distribution of 5-ht 5 receptors in the mouse brain have shown putative 5-ht 5 binding sites in the habenula, hippocampus, septum, olfactory bulb and raphe (Waeber et al, 1998;Grailhe et al, 1999). mRNA localization studies in the rat brain have demonstrated the presence of 5-ht 5A and 5-ht 5B receptor transcripts in different areas, including piriform cortex, habenula and some hippocampal structures (Matthes et al, 1993;Erlander et al, 1993;Kinsey et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Brain NA systems are activated by stress (Morilak et al, 2005). High levels of serotonin receptors subtypes (5-HT5) are reported to be present in the medial habenula of wild type (Waeber et al, 1998). Taken together, the effects of SNRIs in the treatment of chronic pain (Wright et al, 2011) may reflect these drug effects on the habenula.…”
Section: Analgesics and The Habenulamentioning
confidence: 99%
“…These include the NMDA receptor antagonists which decrease activity in the habenula (Weissman et al, 1989; Eintrei et al, 1999); calcitonin gene related peptide CGRP (Skofitsch and Jacobowitz, 1985) as is substance P (Neckers et al, 1979) which is present in high levels in rat habenula. However, the involvement and distribution of these peptides is complex; for example, NK-1 and NK-3 receptor agonists excite habenula neurons and electrophysiological recording suggest that these receptors are found on different populations of neurons in medial habenula (Norris et al, 1993; Waeber et al, 1998). A cholinergic pathway from the medial habenula to the IPN has been defined (Fasolo et al, 1992).…”
Section: Analgesics and The Habenulamentioning
confidence: 99%
“…Altogether the heterogeneous effects of 5-HT on functional classes of olfactory bulb neurons is likely mediated by cell-class specific receptor expression. While there are only four 5-HT receptors in the AL of M. sexta, there are at least ten 5-HT receptors expressed in the olfactory bulb (Appel et al, 1990;Hellendall et al, 1993;Shen et al, 1993;Tecott et al, 1993;Watts et al, 1994;McLean et al, 1995;Wright et al, 1995;Waeber et al, 1998;Bai et al, 2004;Lucaites et al, 2005;Petzold et al, 2009). This expands the complexity by which a single modulator can alter olfactory process across multiple cell types.…”
Section: Serotonergic Modulation Of Olfactory Processingmentioning
confidence: 99%